A comparison between serology (ELISA) and endoscopy and biopsy in the follow up of patients after treatment of H.pylori infection - Sh Savad Koohi (Babol University of Medical Sciences, 2001)
Objective: Helicobacter pylori eradication is recommended in gastric and duodenal ulcer and MALT lymphoma management. For following up for patients after treatment of h.pylori infection, invasive and non-invasive procedures can be performed. The objective of this study was to compare invasive and non-invasive procedures. Methods: 150 patients with h.pylori positive were selected for our study and divided into three groups. In all groups quadruple therapy (Omeprazole, bismuth, metronidazole and amoxicillin) was done. One month later endoscopy and biopsy, serology (H.pylori ELISA IgA) and serology (H.pylori ELISA IgG) were done in first, second and third group respectively and compared for h.pylori eradication. Findings: 127 patients remained as subjects in our study. In first group, endoscopy and biopsy was done again and we found no h.pylori in 70.7% of the cases of the first group, 35.7% and 20.5% of the cases of the second and third group respectively and this difference was statistically meaningful (P<0.001). Conclusion: In spite of the fact that endoscopy and biopsy in comparison to serology is an invasive procedure, it is recommended for short term follow up of patients (One months).